2017
DOI: 10.1021/acsnano.7b04219
|View full text |Cite
|
Sign up to set email alerts
|

Template-Free Synthesis of Highly Porous Boron Nitride: Insights into Pore Network Design and Impact on Gas Sorption

Abstract: Production of biocompatible and stable porous materials, e.g., boron nitride, exhibiting tunable and enhanced porosity is a prerequisite if they are to be employed to address challenges such as drug delivery, molecular separations, or catalysis. However, there is currently very limited understanding of the formation mechanisms of porous boron nitride and the parameters controlling its porosity, which ultimately prevents exploiting the material's full potential. Herein, we produce boron nitride with high and tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
131
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 116 publications
(151 citation statements)
references
References 57 publications
8
131
1
Order By: Relevance
“…In addition, the microporosity of the as‐synthesized samples gets enhanced with an increase in the amount of N precursors due to the generation of the additional porogens in the form of NH 3 , H 2 O, CO, N 2 , etc. The formation of porous BN structure as an outcome of the release of these porogens during the decomposition of the B and N based precursors was revealed ,. It was observed that porosity is a function of thermal decomposition characteristics of the N based precursors .…”
Section: Development Of H‐bn Nanomaterialsmentioning
confidence: 99%
See 4 more Smart Citations
“…In addition, the microporosity of the as‐synthesized samples gets enhanced with an increase in the amount of N precursors due to the generation of the additional porogens in the form of NH 3 , H 2 O, CO, N 2 , etc. The formation of porous BN structure as an outcome of the release of these porogens during the decomposition of the B and N based precursors was revealed ,. It was observed that porosity is a function of thermal decomposition characteristics of the N based precursors .…”
Section: Development Of H‐bn Nanomaterialsmentioning
confidence: 99%
“…The formation of porous BN structure as an outcome of the release of these porogens during the decomposition of the B and N based precursors was revealed ,. It was observed that porosity is a function of thermal decomposition characteristics of the N based precursors . For instance, urea, biuret and melamine decompose at 150°C, 190°C, and 260°C respectively thereby providing a wide range of decomposition temperature for the formation of BN.…”
Section: Development Of H‐bn Nanomaterialsmentioning
confidence: 99%
See 3 more Smart Citations